Comprehensive analysis of the clinical and biological significances of polyamine metabolism in glioma - Fei Bai; Kexin Zhai; Tiantian Yao; Yuxia Zhou; Yongxiang Zhao; Guanghui Yang (Discover Oncology)
Abstract Polyamines, including spermidine, spermine, and putrescine, are polycationic alkylamines in mammalian cells. However, the prognostic impact of polyamine in glioma remains unclear. In the present study, we performed bioinformatic analysis to characterize the expression of polyamine metabolism family members in patients with glioma. A prognostic gene model was conducted based on the 13 prognostic polyamine metabolism genes. The nomogram exhibited excellent performance in predicting the survival rates of glioma patients. Enrichment analysis showed that the characteristics of genes related to polyamine metabolism affected glioma in many ways, especially related to tumor inflammation, hypoxia and IL6/JAK/STAT3 pathway. In vitro experiments demonstrated that targeting SMS protein could effectively inhibit the proliferation and invasion of glioma cells. What’s more, IHC staining was conducted on glioma tissue microarrays to confirm the expression patterns of genes related to polyamine metabolism in glioma tissues. In summary, polyamine metabolism is a powerful prognostic indicator and can be used as a promising target to strengthen the personalized treatment of glioma.The developed system can improve our understanding of the role of polyamine metabolism in gliomas, paving the way for more precise and effective treatment strategies.